Imbalanced production of IL-18 and its antagonist in human diseases, and its implications for HIV-1 infection. (June 2016) - Samarani, Suzanne; Allam, Ossama; Sagala, Patrick; Aldabah, Zainab; Jenabian, Mohammad-Ali; Mehraj, Vikram; Tremblay, Cécile; Routy, Jean-Pierre; Amre, Devendra; Ahmad, Ali
Highlights: IL-18 is normally kept inactive by its antagonist, IL-18BP, in the circulation. It induces production of IL-18BP as a negative feedback response in healthy state. IL-18 levels are increased in the circulation of HIV-infected patients. The patients show compromised negative feedback response. Sustained higher levels of IL-18 despite cART predict treatment failure. Abstract: IL-18 is a pleiotropic and multifunctional cytokine that belongs to the IL-1 family. It is produced as a biologically inactive precursor, which is cleaved into its active mature form mainly by caspase-1. The caspase becomes active from its inactive precursor (procaspase-1) upon assembly of an inflammasome. Because of IL-18's potential pro-inflammatory and tissue destructive effects, its biological activities are tightly controlled in the body by its naturally occurring antagonist called IL-18BP. The antagonist is produced in the body both constitutively and in response to an increased production of IL-18 as a negative feedback mechanism. Under physiological conditions, most of IL-18 in the circulation is bound with IL-18BP and is inactive. However, an imbalance in the production of IL-18 and its antagonist (an increase in the production of IL-18 with a decrease, no increase or an insufficient increase in the production of IL-18BP) has been described in many chronic inflammatory diseases in humans. The imbalance results in an increase in the concentrations of free IL-18 (unbound with its antagonist) resulting in increased biological activities of the cytokine that contribute towards pathogenesis of the disease. In this article, we provide an overview of the current biology of IL-18 and its antagonist, discuss how the imbalance occurs in HIV infections and how it contributes towards development of AIDS and other non-AIDS-associated clinical conditions occurring in HIV-infected individuals undergoing combination anti-retroviral therapy (cART). Finally, we discuss challenges facing immunotherapeutic strategies aimed at restoring balance between IL-18 and its antagonist in these patients.